The Effect of Age and the Delay before Surgery on the Outcomes of Intercostal Nerve Transfers to the Musculocutaneous Nerve: A Retrospective Study of 232 Cases of Posttraumatic Total and Near-total Brachial Plexus Injuries - Bhatia, Anil; Kulkarni, Aditi; Zancolli, Pablo; Martinez, Raul Rodriguez; Clifton, Jorge; El-Gammal, Tarek; Muset, Alex (Indian Journal of Plastic Surgery, 2020)
Introduction Posttraumatic brachial plexus injuries are devastating, as the brain and spinal cord are disconnected from the upper limb. Restoration of elbow flexion has been widely recognized as the primary objective of nerve reconstruction. In the absence of utilizable (ruptured) root stumps in the neck, one has recourse only to nerve transfers. The direct transfer of intercostal nerves to the musculocutaneous nerve is one of the techniques that has been commonly employed over the past four decades. However, the outcomes of this procedure cited in the literature have varied considerably. The patient’s age and the delay from the accident to surgery have been known to affect the results of nerve reconstruction operations. The authors present a study of the effect of these parameters on intercostal nerve transfers.Methods The data of 232 patients with total and near-total brachial plexus injuries treated by the senior author between April 1995 and December 2015 was examined. Intercostal nerve transfers were used for the restoration of biceps function in each of these patients. The outcomes were tabulated, and the correlation with the age and the delay before surgery was examined.Results The strength of the biceps regained was better in patients younger than 30 years old and those operated upon earlier than 6 months from the accident. The differences in outcomes were found to be statistically significant (p = 0.001 for preoperative delay and p < 0.005 for the patient’s age).Conclusion The results give clear proof of the significant effect of the age and preoperative delay on the outcomes of intercostal nerve transfers for restoration of biceps function. These findings can serve as pointers to help the surgeon in choosing the method of nerve reconstruction in a given case.
Keywords: brachial plexus injury; elbow flexion reconstruction; intercostal nerve transfer; preoperative delay